2018
DOI: 10.1590/1807-1929/agriambi.v22n6p373-377
|View full text |Cite
|
Sign up to set email alerts
|

Doses and forms of Azospirillum brasilense inoculation on maize crop

Abstract: A B S T R A C TIn search of a more sustainable agriculture, the use of beneficial microorganisms has been highlighted, because they are low-cost and can reduce the use of fertilizers and increase grain yield. The present study aimed to evaluate the efficiency of A. brasilense inoculation and the best form and dose of inoculation in maize, measuring the impact on some physical characteristics and on its nutrition. The experiment was conducted in a greenhouse, in Ilha Solteira, SP, Brazil, in a completely random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
9
0
7
Order By: Relevance
“…Azospirillum brasilense increased leaf dry weight in the presence of this element and no significant effect was observed when only the microorganism or micronutrient were applied to the seeds (Table 1). Santini et al (2018) reported an increase in the zinc demand of maize plants stimulated by inoculation with Azospirillum brasilense, indicating that the micronutrient had a greater effect in the presence of these rhizobacteria. By contrast, Bacillus subtilis reduced stem dry weight but did not affect total dry weight when associated or not with zinc ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Azospirillum brasilense increased leaf dry weight in the presence of this element and no significant effect was observed when only the microorganism or micronutrient were applied to the seeds (Table 1). Santini et al (2018) reported an increase in the zinc demand of maize plants stimulated by inoculation with Azospirillum brasilense, indicating that the micronutrient had a greater effect in the presence of these rhizobacteria. By contrast, Bacillus subtilis reduced stem dry weight but did not affect total dry weight when associated or not with zinc ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, for instant carboxylation efficiency, EiC, the highest value was obtained with the BRM32114 + pool of T. asperellum mixture (0.08 (μmol m -2 s -1 ) (μmol mol -1 ) -1 ); however, there was no significant difference from that of the control treatment. The increase in enzymatic activity associated with photosynthesis, enhanced by biotic factors such as the introduction of beneficial microorganisms to the culture medium (Galmés et al, 2011;Nascente et al, 2017a,b;Santini et al, 2018;Buzo et al, 2019;Santos Júnior et al, 2019), can result in greater growth, which can increase productivity. Therefore, the mixed treatments of BRM32114 + pool of T. asperellum, 1301 + Ab-V5 and Ab-V5 + pool of T. asperellum stood out and provided the upland rice plants with higher values both in the photosynthetic rate and in the carboxylation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Content of macronutrients in biomass of upland rice plants, cultivar BRS A501 CL, submitted to the inoculation of beneficial microorganisms, isolated or in mixture * -Significant difference from the control treatment by the Dunnett test at p ≤ 0.05; averages followed by the same letter do not differ by the LSD test (p ≤ 0.05); 1 to 26 -Number of treatments; The black bar refers to the control treatment. Treatments: isolated BRM32114 (1); isolate BRM32110 (2); pool of T. asperellum (3); isolate 1381 (4); Ab-V5 isolate (5); isolate 1301 (6) and mix BRM32114 + BRM32110 (7); mix BRM32114 + 1381 (8); mix BRM32114 + pool of T. asperellum (9); mix BRM32114 + 32110 + Ab-V5 (10); mix 32110 + Ab-V5 (11); mix 32110 + T. asperellum pool (12); mix 32110 + Ab-V5 + pool of T. asperellum (13); mix Ab-V5 + pool of T. asperellum (14); mix BRM32114 + pool of T. asperellum (15); mix 1381 + 1301 (16); mix 1381 + Ab-V5 (17); mix 1301 + Ab-V5 (18); mix 1381 + BRM32114 (19); mix 1301 + BRM32114 (20); mix 1381 + 32110 (21); mix 1301 + 32110 (22); mix 1381 + T. asperellum pool (23); mix 1301 + pool of T. asperellum (24); mix BRM32114 + BRM32110 + 1381+ pool of T. asperellum + 1301+ Ab-V5 (25) and control (without microorganism) 26water and nutrients, which can provide greater resistance to environmental stresses, such as increased temperature, reduced relative humidity, reduced porous soil space, and increased salt concentration (Chagas et al, 2016;Rosa et al, 2020;Pereira et al, 2020;Santini et al, 2018;Buzo et al, 2019;Santos Júnior et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…There was a significant difference between treatments for the thousand grain weight component with the application of nitrogen combined or not with A. brasilense (BF+CF, BF+BI+CF, BI+CF) compared to the others (BF+BI, BI, NFI, and CF) (Table 3). The thousand-grain weight is a valuable parameter since it is possible to obtain higher productivity increasing the accumulated reserves in the grains from the same number of the fertilized ovule (Santini et al, 2018). This was observed when we used nitrogen in at least two associated forms (BF+CF, BF+BI+CF, or BI+CF).…”
Section: /6mentioning
confidence: 88%